PENGARUH PROFITABILITAS, TOTAL ASSET TURN OVER (TATO), ARUS KAS OPERASI, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN: (Studi Empiris Pada Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia periode 2017-2022) - Desi Susilowati; Rinny Meidiyustiani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to determine the effect of profitability, total asset turnover (TATO), operating cash flow, company size on company value in the property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period as many as 84 companies. The sampling technique in this study used a purposive sampling method and obtained a sample of 44 companies. The analysis technique used is multiple linear regression analysis using Statistical Package for the Social Sciences (SPSS) software version 22.0. The results of this study indicate that profitability and operating cash flow have no effect on firm value, while total asset turnover (TATO) and firm size have a positive effect on firm value.